EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU MEDIA PAPAN KERAGAMAN BUDAYA DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA KELAS 5 SEKOLAH DASAR - Wandiana Putri, Nisa; Ika Ari Pratiwi; Fitriyah Amaliyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on a learning process that still uses the lecture method and teachers do not use learning media, so students are not optimal in solving problems. This research aims to determine the effectiveness of the Problem Based Learning Model supported by Cultural Diversity Board Media in improving students' critical thinking skills in class V. This research uses a quantitative Pre-Experimental approach with a One Group Pretest-Posttest Design. The research subjects consisted of 19 class V students. Test data includes pretest and posttest, while non-test interviews and observations. Data analysis techniques include normality test, paired sample test, and N-Gain test. The results of the analysis showed that the average pretest score was 46, while the posttest increased to 81. The results of the paired sample test produced a significance value of -11.763, which shows that there is an influence from implementing PBL with the help of cultural diversity board media in improving critical thinking skills. The n-gain test results show a score of 0.6436, which is in the medium category. Thus, it can be concluded that the application of the PBL learning model assisted by diversity board media is quite effective in improving the critical thinking skills of class V students.